Associations of lifestyle with physical, hearing, visual, and mental functional impairments among older adults: Findings from two prospective cohort studies. (February 2023) - Cai, Hui; Cui, Yong; Cravens, Lauryn; Yang, Gong; Yu, Danxia; Gao, Yu-Tang; Zheng, Wei; Shu, Xiao-Ou
Highlights: The reported study, to the best of our knowledge, is by far the largest and longest follow-up study that prospectively investigated the influence of lifestyle factors on age-related functional impairments among older adults. Healthy lifestyle, including healthy dietary habits, no smoking, limited drinking, exercise, and normal body mass index (BMI), is associated with a decreased likelihood of aging-related functional impairments in walking, hearing/vision, memory, and decision-making at a median follow-up of 14.4 years. The lifestyle-aging related functional impairment associations are similar between participants with and without cardiometabolic diseases at the baseline survey. Abstract: Objective: To examine the associations between lifestyle habits and functional impairments among older adults. Methods: The study includes 20, 545 women and 14, 374 men aged 70 years or older at the time of the function assessment. Participants were from two prospective cohort studies: the Shanghai Women's Health Study (SWHS, enrollment from 1996 to 2000) and the Shanghai Men's Health Study (SMHS, enrollment from 2002 to 2006). Lifestyle information was collected at study enrollment and a healthy lifestyle score (HLS) was derived. Functional impairment information was collected at the follow-up survey conducted in 2012-2017. Logistic regression analyses were applied to estimate the associations of HLS with functional impairments. Results: The average age at lifestyle and functional impairment assessment was 62.3 (range: 49.9-70.9) and 77.7 (range: 70.0-89.4) for women and 67.5 (range: 55.1-74.9) and 77.4 (range: 70.0-88.6) for men. After a median follow-up of 14.4 years, we found that the HLS was inversely associated with overall severe functional impairment: odds ratio (95% confidence interval), 0.78(0.71-0.86) and individual severe functional impairment: 0.67(0.62-0.73) for independent walking, 0.85(0.77-0.94) for hearing/vision, 0.79(0.70-0.88) for memory, and 0.74(0.67-0.82) for decision-making impairment, comparing the highest with the lowest HLS categories. Such associations were similar among individuals with/without cardiometabolic diseases at baseline. The associations between each lifestyle factor and functional impairments differed. Conclusion: A healthy lifestyle was associated with reduced odds of physical and mental impairment among older Chinese adults, emphasizing the importance of promoting and maintaining a healthy lifestyle to prevent or postpone age-related functional impairments.